2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346392
|View full text |Cite
|
Sign up to set email alerts
|

Validation of heart rate extraction using video imaging on a built-in camera system of a smartphone

Abstract: As a smartphone is becoming very popular and its performance is being improved fast, a smartphone shows its potential as a low-cost physiological measurement solution which is accurate and can be used beyond the clinical environment. Because cardiac pulse leads the subtle color change of a skin, a pulsatile signal which can be described as photoplethysmographic (PPG) signal can be measured through recording facial video using a digital camera. In this paper, we explore the potential that the reliable heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(44 citation statements)
references
References 5 publications
1
42
0
1
Order By: Relevance
“…The use of mobile phones or general activity trackers elaborated the high accessibility of users. Recent studies demonstrated the validity of using accelerometer in iPhone for the physical activity monitoring [28], the extraction of heart rate [35], and applications for Parkinson and Holmes tremor [36]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of mobile phones or general activity trackers elaborated the high accessibility of users. Recent studies demonstrated the validity of using accelerometer in iPhone for the physical activity monitoring [28], the extraction of heart rate [35], and applications for Parkinson and Holmes tremor [36]. …”
Section: Discussionmentioning
confidence: 99%
“…More recently, a number of studies performed in biomedical engineering laboratories have demonstrated the feasibility of non-contact measuring of HR with a webcam (i.e., a digital video camera that streams its images to a computer). Poh et al (2010) demonstrated the validity of HR measurements from a webcam by comparing them with measurements obtained at the same time from (but not time synchronized with) a blood pulse oximetry sensor (also see Kwon et al, 2012; Poh et al, 2011a). Subsequent studies have used webcams to study changes in HR due to exercise (Sun et al, 2011, 2012) and the development of devices designed to aid with health monitoring (Poh et al, 2011b; Verkruysse et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…This principle motivated the use of digital cameras to measure the plethysmographic signals from face videos under ambient light conditions [4][5][6]. Several methodologies for estimating heart rate from face videos have been developed over the years [7][8][9][10][11][12]. In particular, [13] provides a comprehensive overview of the history of the research done in this area and compares the performance of some of these approaches.…”
Section: Introductionmentioning
confidence: 99%